A systematic review on OCDMA network having different detection techniques - Swati Thakur , Ashima Shah (International Journal of Advanced Science and Technology, 2020)
OCDMA i.e. optical code division multiple access network become the great area of interest intoday’s optical communication networks. It fulfill all the basic criteria which are required for a goodcommunication to take place i.e. no. of consumers can access to the data asynchronously orsynchronously with high level of data security. As in OCDMA network every user is provided withunique address code so, even in burst of data the chances of leakage of data is very rare. But at thereceiver end data get degraded due to the noise in communication channel and in the components. Inthis paper, there is differentiation of four different detection techniques used in OCDMA basednetwork discussed. Those detection techniques are namely direct detection method, AND subtractionmethod , modified AND detection method , single photodiode detection(SPD). These detectiontechniques helps to recover the data with removal of noise which occur during the data transmission